Functional Pragmatic Analysis in Building Students' Contextual Understanding of Literary Works - Rahayu Kuswardani; Muhaimin Abdullah; Rizky Ramadhan; Fithriyah Inda Nur Abida; Risman Iye (UIN Salatiga, 2024)
This study aims to analyze the role of a functional pragmatic approach in developing students' contextual understanding of literary works. The functional pragmatic approach emphasizes the importance of context in interpreting text meaning, considering the social, cultural, and situational backgrounds that influence communication in literature. In literature education, this method helps students go beyond understanding the literal content of a text. It encourages them to explore the deeper layers of meaning by considering the relationship between the author, the reader, and the broader societal context in which the text was produced. The research employs a qualitative case study design, engaging literature students as participants to examine how this approach is implemented in real classroom settings. The study utilizes several data collection techniques, including observations, interviews, and document analysis. These methods allow the researcher to comprehensively understand how the functional pragmatic approach is applied during literature lessons and its impact on students' comprehension. The findings indicate that this approach significantly enhances students' ability to critically analyze the meaning of texts and deepen their understanding of the social and cultural contexts embedded in the literature.Additionally, it fosters an appreciation for the values and messages conveyed through literary works. The study's implications suggest that incorporating a functional pragmatic approach in literature instruction could powerfully support the development of students' contextual understanding and critical thinking skills. By emphasizing the importance of context in literary analysis, this approach can help students engage with texts on a deeper level, making literature more meaningful and relevant to their lives.